METODE MULTISENSORI TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN 1-10 PADA ANAK AUTIS - Nurjanah, Eka (Jurnal Pendidikan Khusus, 2017)
ABSTRACT The problem which was experienced by the autism children was the children did not recognize number 1-10 yet. The learning used in recognizing number was by multisensory method. A multisensory method was one of the learning methods using all senses the children had in learning process. The purpose of this research was to prove the influence of multisensory method toward recognizing number 1-10 ability to autism children. This research method used quantitative approach with quantitative descriptive kind. The data was collected by writing test, observation, and documentation. Writing test was used to obtain the data of recognizing number 1-10 ability to autism children before giving treatment and after giving treatment. The research result indicated that the average pre test was 51,33 and the average post test was 78,67. This indicated that there was significant enhancement. Zh value = 2,20 was greater than critic value 5% Zt = +1,96 so it could be stated there was influence of multisensory method toward recognizing number to autism children. Keywords: multisensory method, recognizing number